(untitled) (International Journal of Applied Research in Management and Economics, 2020)
This paper focuses on a changes in the structure of the labor market, where the main criterion is being education, which determines the skill level of each worker. This fact allows considering highly educated workers as high-skilled workers. Due to the availability of the data set from EU KLEMS, we focus on all EU countries between 2008 and 2015. This contribution answers resolves the question, what the trends within jobs are in different industries of EU countries based on the education criterion. The results imply (with exceptions) skill-upgrading across all industries and in most countries (only 5 countries stagnated). Proportions of high-skilled workers increased in the countries concerned by about 3-–10 p. p. Similarly, wage growth was proportional to skills. All this provides some evidence about the skill -upgrading process (which is consistent with the SBTC hypothesis), rather than skill-polarization. Some evidence about on skill-upgrading opens raises the question of how the growing number of high-educated workers have affected productivity. The results show that in most cases there is a direct relationship, but there are country and industry exceptions.